Drugs affecting the autonomic nervous system. Issue 10 (October 2019) - Charlton, Matthew; Thompson, Jonathan P.
Abstract: The autonomic nervous system (ANS) is a complex system of nervous and humoral mechanisms that modulates the function of the autonomous or visceral organs. Autonomic control of organs aims to maintain homoeostasis in health. Many drugs used in clinical practice can have either primary or secondary effects on the function of autonomic nervous system.